2019
DOI: 10.7717/peerj.6396
|View full text |Cite
|
Sign up to set email alerts
|

Genetic alteration of histone lysine methyltransferases and their significance in renal cell carcinoma

Abstract: BackgroundHistone lysine methyltransferases (HMTs), a category of enzymes, play essential roles in regulating transcription, cellular differentiation, and chromatin construction. The genomic landscape and clinical significance of HMTs in renal cell carcinoma (RCC) remain uncovered.MethodsWe conducted an integrative analysis of 50 HMTs in RCC and discovered the internal relations among copy number alterations (CNAs), expressive abundance, mutations, and clinical outcome.ResultsWe confirmed 12 HMTs with the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…The heterogeneity of the study populations may have at least partly contributed to this discordance. However, our study indicated that high levels of NSD3 expression indicated poor prognosis for patients with PAAD, KIRP, and UVM, which is consistent with previous studies (32,36,37). A recent study concluded that ablation of NSD3 in a mouse model of LUSC attenuates tumor growth and results in prolonged survival (16).…”
Section: Discussionsupporting
confidence: 91%
“…The heterogeneity of the study populations may have at least partly contributed to this discordance. However, our study indicated that high levels of NSD3 expression indicated poor prognosis for patients with PAAD, KIRP, and UVM, which is consistent with previous studies (32,36,37). A recent study concluded that ablation of NSD3 in a mouse model of LUSC attenuates tumor growth and results in prolonged survival (16).…”
Section: Discussionsupporting
confidence: 91%
“…The heterogeneity of the study populations may have at least partly contributed to this discordance. However, our study indicated that high levels of NSD3 expression indicated poor prognosis for patients with PAAD, KIRP, and UVM, which is consistent with previous studies (32,36,37). A recent study concluded that ablation of NSD3 in a mouse model of LUSC attenuates tumor growth and results in prolonged survival (16).…”
Section: Discussionsupporting
confidence: 91%
“…However, surgery is not suitable for metastatic RCC, and RCC is insensitive to both chemotherapy and radiotherapy ( Sun et al, 2020 ). Meanwhile, targeted therapies have obviously improved the prognosis of metastatic RCC patients ( Yan et al, 2019 ). Thus, it is essential to explore effective predictive biomarkers for RCC patient prognosis and targeted therapy of RCC.…”
Section: Introductionmentioning
confidence: 99%